Survival and Functionality of Human Induced Pluripotent Stem Cell-Derived Oligodendrocytes in a Nonhuman Primate Model for Multiple Sclerosis. (11th July 2016) - Thiruvalluvan, Arun; Czepiel, Marcin; Kap, Yolanda A.; Mantingh-Otter, Ietje; Vainchtein, Ilia; Kuipers, Jeroen; Bijlard, Marjolein; Baron, Wia; Giepmans, Ben; Brück, Wolfgang; 't Hart, Bert A.; Boddeke, Erik; et al.
Abstract : In this study, human induced pluripotent stem cells (hiPSCs) were differentiated into oligodendrocyte precursor cells (OPCs) and their proper functionality was validated in vitro and in vivo in mouse models for multiple sclerosis (MS). hiPSC-derived OPCs were injected intracerebrally in a marmoset model for progressive MS: The grafted OPCs specifically migrated toward the MS-like lesions in the corpus callosum, where they myelinated denuded axons. Abstract: Fast remyelination by endogenous oligodendrocyte precursor cells (OPCs) is essential to prevent axonal and subsequent retrograde neuronal degeneration in demyelinating lesions in multiple sclerosis (MS). In chronic lesions, however, the remyelination capacity of OPCs becomes insufficient. Cell therapy with exogenous remyelinating cells may be a strategy to replace the failing endogenous OPCs. Here, we differentiated human induced pluripotent stem cells (hiPSCs) into OPCs and validated their proper functionality in vitro as well as in vivo in mouse models for MS. Next, we intracerebrally injected hiPSC-derived OPCs in a nonhuman primate (marmoset) model for progressive MS; the grafted OPCs specifically migrated toward the MS-like lesions in the corpus callosum where they myelinated denuded axons. hiPSC-derived OPCs may become the first therapeutic tool to address demyelination and neurodegeneration in the progressive forms of MS. Significance: This study demonstrates for the first time that human induced pluripotent stem cell (iPSC)-derived oligodendrocyte precursor cells (OPCs), after intracortical implantation in a nonhuman primate model for progressive multiple sclerosis (MS), migrate to the lesions and remyelinate denuded axons. These findings imply that human iPSC-OPCs can be a therapeutic tool for MS. The results of this feasibility study on the potential use of hiPSC-derived OPCs are of great importance for all MS researchers focusing on the stimulation of remyelination in MS patients. Further optimization and research on practical issues related to the safe production and administration of iPSC-derived cell grafts will likely lead to a first clinical trial in a small group of secondary progressive MS patients. This would be the first specific therapeutic approach aimed at restoring myelination and rescuing axons in MS patients, since there is no treatment available for this most debilitating aspect of MS.